Kajian Intertekstual Lirik Lagu Opick pada Album "Semesta Bertasbih" dan Al Quran - Ustati, Danar Dwi Vivi, Prof. Dr. Markhamah, M.Hum (2016)
This study aimed to describe the relationship intertextuality and the similarity of text contained in the text songs Opick "Semesta Bertasbih" with the Al quran This study is descriptive qualitative research. Object intertextuality research studies on song album "Semesta Bertasbih" Opick. The data collected for this study is the lyrics of the songs contained in the album Opick "Universe Bertasbih" containing textual and repetition to the text that is in the Al quran. Sources of data in this study are the songs Opick in Album "Semesta Bertasbih" and the Al quran. Data collection techniques used in the study refer to the techniques and note. Triangulation is used in this research is triangulation of data sources. Based on the results of data analysis can be concluded that: 1) Overview Intertextuality contained in Album "Semesta Bertasbih" is very interesting, because every creation of the lyrics of a song is always based on the verse Al quran surah Al-Fatihah, Al Baqarah, Aal, Ajjumah, An- Naml An-Nahl, Al Hajj, Al-Israa, Al-Hadid, An-Nisa, An Nur, Al-Hashr, Shaad, At Taghabun, Ar-Ra'd, Al Fathir, Al-Hakim, Al-Tawbah, Az-Zumar Al Muthafifin, Ibrahim, Ar Rum, Al-Ahzab, Al Zalzalah, Al Araf, Yunus, Al Mukminun, Yassin and Al-Hujurat. 2) The repetition of the text contained in the lyrics Opick On Album "Semesta Bertasbih" and an Al qur includes reps comprising intact repetition, anaphora and tautotes, synonymy and collocation.